Investment guide : Sabah, Malaysia (Kota Kinabalu : Govt. of Sabah, 1977)
This book guide describes the background, physical features, climate and economy of Sabah, Malaysia.
ne 19/08/2021
Loans
Keywords: Investments, Foreign; Economic history; Sabah (Malaysia)